2020
DOI: 10.1016/j.csr.2020.104171
|View full text |Cite
|
Sign up to set email alerts
|

Storm-induced hydrodynamic changes and seabed erosion in the littoral area of Yellow River Delta: A model-guided mechanism study

Abstract: induced hydrodynamic changes and seabed erosion in the littoral area of Yellow River Delta: A model-guided mechanism study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…This demonstrates that wave-induced shear stress is the main contributor to total bed shear stress during large gales. This means that waves generate sufficient shear stress to resuspend sediment, which is consistent with previous studies with remote sensing (Chu et al, 2006;Zhang et al, 2018;Li et al, 2021), field investigations (Yang et al, 2011;Liu et al, 2020;Niu et al, 2020;Zhang et al, 2021), and numerical simulations (Jiang et al, 2004;Fan et al, 2020).…”
Section: Sediment Resuspensionsupporting
confidence: 91%
“…This demonstrates that wave-induced shear stress is the main contributor to total bed shear stress during large gales. This means that waves generate sufficient shear stress to resuspend sediment, which is consistent with previous studies with remote sensing (Chu et al, 2006;Zhang et al, 2018;Li et al, 2021), field investigations (Yang et al, 2011;Liu et al, 2020;Niu et al, 2020;Zhang et al, 2021), and numerical simulations (Jiang et al, 2004;Fan et al, 2020).…”
Section: Sediment Resuspensionsupporting
confidence: 91%
“…The sediment erosion parameters and other parameters are initially selected based on a similar study (Fan, 2019). The parameters are set as follows: sediment particle size of 0.05 mm, sediment density of 1600 kg/m 3 , sediment settling velocity of 0.15 mm/s, erosion rate of 5×10 -4 m 2 /s, critical initial stress of 0.115 N/ m 2 , and porosity of 0.5.…”
Section: Model Setupmentioning
confidence: 99%
“…Strong storm surges prevailed around the Bohai Sea during the past 2000 years (Feng, 1982;Liu, 1989). Based on the observing hydrodynamic and sediment data, the simulation results of an abandoned Yellow River Delta lobe, revealed that local storms enhanced tidal residual currents and considerably weakened tidal shear front, intensified the sediment resuspension and dispersal (Fan et al, 2020). Under storm conditions, surface suspended sediment concentration was 2 times as large as that in normal conditions.…”
Section: Major Geomorphic Processes and A Model Of The Evolution Of T...mentioning
confidence: 99%